Factors Associated with Low Coverage of Intermittent Preventive Treatment with Sulfadoxyne-Pyrimethamine in Pregnancy in Dassa-Glazoué.................1 - ATADE, R.; OGOUDJOBI, OGOURINDÉ MATHIEU; DANGBEMEY, D. Patrice; DANGBEMEY, Djima Patrice; Djodi, Salamatou; KLIKPEZO, Roger; SALIFOU, KABIBOU (My University, 2021)
Abstract: Introduction: Malaria during pregnancy is a major public health concern in most endemic areas, including Benin. To overcome this, the World Health Organization (WHO) recommends several prevention strategies, including the administration of sulfadoxine-pyrimethamine (SP) during pregnancy. Objective: To study the factors associated with low coverage of Intermittent Preventive Treatment with sulfadoxine-pyrimethamine (IPT-SP) against Malaria in pregnant women at Dassa-Glazoué area hospital in 2020. Study Method: This was a descriptive, analytical study with retrospective data collection that took place from May 25 to September 25, 2020. Results: During our study, three hundred and forty (340) pregnant women were investigated. The mean age was 27.67±6.12 years. The pregnant women included in the study were traders/dealers (35%) with a primary level of education (35%) and living in a common-law relationship (77.65%). The prevalence of IPT-SP coverage in antenatal care (ANC) was 35.00%. The number of ANC (less than 4) attended by the pregnant women (p=0.00), the age of more than 3 months from pregnancy to the first ANC (p=0.00) and non-compliance with ANC (p=0.00) were the factors associated with this low coverage. Conclusion: ANC is a special time for the administration of SP. New strategies must be put into place for the correct use of this service by pregnant women.
Keywords: Intermittent Preventive Treatment; Sulfadoxine-Pyrimetamine; Antenatal Consultation; Malaria